Research on the size effect of rock-filled concrete compressive strength: Considering the influence of rockfill ratios and rock shapes - Li-xiu Wu; Shuang Zou; You-bin Li; Yi-hui Liang (Case Studies in Construction Materials, 2025)
Research on the size effect of rock-filled concrete (RFC) compressive strength can provide experimental references for numerical simulations at the macroscopic dam scale. Current studies on the influencing factors of compressive strength size effects predominantly focus on conventional concrete, with limited investigations specifically addressing RFC. This paper investigates the influence of rockfill ratios and rock shapes on the size effect of the compressive strength of RFC. Compression tests were conducted on 450 × 450 × 450 mm specimens and a three-dimensional three-phase RFC mesoscopic model was established to simulate compression tests under varying conditions. The results indicate that the specimens ultimately develop a failure pattern closely resembling an ‘X’ shape. The compressive strength of RFC increases with higher rockfill ratios, showing an enhanced range of 4.9–10.9 %, while the rockfill ratio also exerts a significant influence on the size effect. Notably, higher rockfill ratios exhibit more significant crack suppression due to the enhanced skeletal structure formed by densely packed rockfill. The influence of rock shape, on both the compressive strength and the size effect of RFC, is relatively minor. However, compared to pebble rocks, RFC with gravel rocks tends to fracture into finer fragments with an increased cracking area under compression. In addition, compressive strength predictions, derived from the three size effect laws of Weibull, Bažant and Carpinteri, are systematically compared with the simulated values. The results demonstrate that Bažant’s size effect law exhibits superior applicability for predicting the compressive strength of RFC. Furthermore, a comparative analysis between the simulated and predicted compressive strengths of the full-scale RFC test block confirms that the compressive strength of RFC cutting specimens possesses strong representativeness and can be reliably applied in practical engineering scenarios.